COVID‐19 and hepatic involvement: The liver as a main actor of the pandemic novel. (26th September 2020) - Napodano, Cecilia; Pocino, Krizia; Stefanile, Annunziata; Marino, Mariapaola; Miele, Luca; Gulli, Francesca; Basile, Valerio; Pandolfi, Franco; Gasbarrini, Antonio; Rapaccini, Gian Ludovico; Basile, Umberto
Abstract: In the natural history of SARS‐CoV‐2 infection, liver injury is frequent but quite mild and it is defined as any liver damage occurring during disease progression and treatment of infection in patients with or without pre‐existing liver diseases. The underlying mechanisms for hepatic injury in patients with COVID‐19 are still unclear but the liver damage in SARS‐CoV‐2 infection seems to be directly caused by virus‐induced cytopathic effects. In this review, we will summarize all data of updated literature, regarding the relationship between SARS‐CoV‐2 infection, acute response and liver involvement. An overview will be given on liver injury, liver transplant and the possible consequences of COVID‐19 in patients with pre‐existing liver diseases.